Clinical classification of generator and electrode failures. - Rickards A; Norman J (Pacing & Clinical Electrophysiology, 1980)
A clinically based failure classification system is suggested for cardiac pacing generators and electrodes, and the method of reporting actuarial survival is reviewed. The difficulties of calculating potential generator lifetimes and the consequent definition of premature generator failures are discussed and p pragmatic solution is offered.